Peruvian architecture in times of climate change: resilience and adaptation - Hertz, John B. (2022)
The climate changes are creating a new situation in the world and in Peru. The natural phenomena registered in our country have showed serious problems in the way to face them and the social and economic losses have been increasing. It is from the architecture that it can be made approaches that face the current reality, radically transforming the way we design spaces that, in all cases, should protect us from the context that surrounds us. In that sense, the objective is to make the buildings, that are constructed, bioclimatic, resilient, that can control their energy consumption and can adapt themselves to the changes of temperature that faces our planet.